Factors Affecting the Result of Nursing Licensure Examination among Bachelor Graduates from Faculty of Nursing, Mahidol University - Kongkar, Ruttanaporn; Charoenkitkarn, Vishuda; Tosuksri, Wandee; Sareewiwatthana, Penchun (Nursing Science Journal of Thailand, 2013)
Purpose: This study aimed to explore factors affecting the result of nursing licensure examination among bachelor graduates from Faculty of Nursing, Mahidol University. Design: Descriptive research. Methods: The sample was 204 registered nurses who graduated from Faculty of Nursing, Mahidol University in academic year 2008 and 2009. Data were collected using questionnaires and analyzed using descriptive statistics, and logistic regression. Main findings: Grade point average throughout the program and the result of comprehensive examination taken when they were undergraduates could correctly predict the result of nursing licensure examination upon graduation by 80.5 percent. For each one increasing grade point average, they were able to pass the nursing licensure examination 4.86 times; and those who passed the comprehensive examination at the first time were able to pass the nursing licensure examination 3.97 times compared to those who failed. Conclusion and recommendations: Based on these findings, program administrators and teachers should emphasize the undergraduate nursing students to pay attention consistently and put effort on their course works with good start at their first year. The knowledge and learning experience they gain throughout the program will be robust basis for them to pass the comprehensive examination taken before and the nursing licensure examination taken after the graduation. Keywords: examination, nursing licensure บทคัดย่อ วัตถุประสงค์: เพื่อศึกษาปัจจัยที่มีอิทธิพลต่อผลการสอบผ่านความรู้ของผู้ขอขึ้นทะเบียน และรับใบอนุญาตเป็นผู้ประกอบวิชาชีพการพยาบาลและการผดุงครรภ์ชั้นหนึ่งของบัณฑิตคณะพยาบาลศาสตร์ มหาวิทยาลัยมหิดล รูปแบบการวิจัย: การวิจัยเชิงบรรยาย วิธีดำเนินการวิจัย: กลุ่มตัวอย่างคือ พยาบาลวิชาชีพซึ่งจบการศึกษาจากคณะพยาบาลศาสตร์ ปีการศึกษา 2551 และ 2552 จำนวน 204 คน เก็บข้อมูลโดยใช้แบบสอบถาม วิเคราะห์ข้อมูลโดยใช้สถิติเชิงพรรณา และ logistic regression ผลการวิจัย: เกรดเฉลี่ยสะสมตลอดหลักสูตรและผลการสอบรวบยอดของพยาบาลวิชาชีพ กลุ่มตัวอย่างสามารถทำนายผลการสอบผ่านความรู้ของผู้ขอขึ้นทะเบียน และรับใบอนุญาตเป็น ผู้ประกอบวิชาชีพการพยาบาลและการผดุงครรภ์ชั้นหนึ่งได้ถูกต้องร้อยละ 80.5 โดยในแต่ละ 1 หน่วยของเกรดเฉลี่ยสะสมที่เพิ่มขึ้น จะมีโอกาสสอบผ่านความรู้เพื่อขอขึ้นทะเบียนฯ จากสภาการพยาบาลถึง 4.86 เท่า และพยาบาลวิชาชีพกลุ่มตัวอย่างที่สอบผ่านการสอบ รวบยอดครั้งที่ 1 ของคณะฯ ทุกรายวิชา มีโอกาสที่จะสอบผ่านความรู้ของผู้ขอขึ้นทะเบียนฯ จากสภาการพยาบาลมากกว่าพยาบาลวิชาชีพกลุ่มตัวอย่างที่สอบไม่ผ่าน 3.97 เท่า สรุปและข้อเสนอแนะ: การจัดการเรียนการสอนอาจารย์ผู้สอนควรเน้นให้นักศึกษาเห็นความสำคัญของการเรียนการสอนทุกรายวิชา ตั้งแต่ชั้นปีที่หนึ่งอย่างต่อเนื่องจนจบหลักสูตร ความรู้และประสบการณ์การเรียนรู้ต่างๆ ที่ได้รับจะเป็นพื้นฐานสำคัญสำหรับการสอบรวบยอดของคณะฯ และการเตรียมความพร้อมในการสอบผ่านความรู้ของผู้ขอขึ้นทะเบียน และรับใบอนุญาตประกอบวิชาชีพการพยาบาลและการผดุงครรภ์ชั้นหนึ่ง คำสำคัญ: การสอบ ใบอนุญาตเป็นผู้ประกอบวิชาชีพการพยาบาลและการผดุงครรภ์ชั้นหนี่ง